Affective repurposing: A procedural conversation between texts, materials, and creations in the poetics of Image and place in the creative process of Peepshow Theater (Móin-Móin Magazine - Studies in the Art of Puppetry, 2024)
Abstract: This scribbled procedure is a documentary record of the time and academic place in the journey of a doll artist in the creation of his poetics. In the whirlwind in which this process was established, cutting, pasting, superimposing, copying, tearing, mixing and resorting to everything that your eyes observe, your touch identifies and your senses absorb, becomes a fundamental procedure in the search for the creation of a poetic based on affective reuse. Intertwining of contents with the intention of a practice, lived, experienced and elaborated simultaneously in the time and space of this academic process, based on the coexistence and approximations of the theoretical and practical framework of Animation Theater and the poetry of Manoel de Barros with poetic devices of the image, serving as inducers of an artistic practice with Teatro de Caixa (Lambe-lambe), giving indications on what we call material and immaterial affective reuse for the creation process.
Keywords: animated theater; peepshow theater; creative process; affective repurposing